HUBUNGAN PENGGUNAAN MUKTIMEDIA INTERAKTIF BERBASIS POWERPOINT DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII DI SMP NEGERI 15 MAKASSAR - Pratiwi, Nur Hikmah; Mustamin; Raehana, Syarifa; Syahid, Akhmad; Azhar, Muh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the use of PowerPoint-based interactive multimedia in learning Islamic Religious Education, the level of students' interest in learning, and the relationship between the two. This study uses a quantitative approach with a correlational type. The research population was all students of grade VIII of SMP Negeri 15 Makassar, with a sample of 72 students. The data collection technique uses questionnaires, observations, and documentation, while data analysis uses Product Moment correlation. The results showed that the use of PowerPoint-based interactive multimedia was in the good category with an average score of